Understanding and treating incels : case studies, guidance, and treatment of violence risk in the involuntary celibate community /: case studies, guidance, and treatment of violence risk in the involuntary celibate community. (2020) - Van Brunt, Brian; Taylor, Chris, 1967-
No abstract available